Phyllanthus niruri Linn.: Antibacterial Activity, Phytochemistry, and Enhanced Antibiotic Combinatorial Strategies - Gagan Tiwana; Ian E. Cock; Matthew J. Cheesman (MDPI AG, 2024)
Antimicrobial resistance (AMR) is a global public health threat caused by the misuse and overuse of antibiotics. It leads to infections becoming difficult to treat, causing serious illness, disability, and death. Current antibiotic development is slow, with only 25% of current antibiotics exhibiting novel mechanisms against critical pathogens. Traditional medicinal plants' secondary metabolites offer potential for developing novel antibacterial compounds. These compounds, often with strong antimicrobial activity, can be used to develop safe and effective antibacterial chemotherapies. This study investigated the antibacterial activity of Phyllanthus niruri Linn. extracts against a panel of bacterial pathogens using disc diffusion and microdilution assays and quantified by calculation of minimum inhibition concentration (MIC). Additionally, the effects of combinations of the extracts and selected conventional antibiotics were examined by sum of fractional inhibition concentration (ƩFIC) calculation and isobologram analysis. Liquid chromatography-mass spectrometry (LC-MS) phytochemistry analysis was used to identify noteworthy compounds in the active extracts and the Artemia nauplii bioassay was used to evaluate toxicity. The aqueous and methanolic extracts exhibited notable antibacterial activity in the broth microdilution assay against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) (MIC = 669 µg/mL and 738 µg/mL, respectively). The methanolic extract also showed noteworthy antibacterial action in the broth assay against Klebsiella pneumoniae (MIC = 738 µg/mL). The aqueous extract had noteworthy growth inhibitory activity against Bacillus cereus (MIC = 669 µg/mL), whilst the methanolic extract demonstrated good antibacterial activity against that bacterium (MIC = 184 µg/mL). The aqueous and methanol extracts showed minimal antibacterial action against Shigella flexneri and Shigella sonnei. The extracts were subjected to LC-MS analysis, which revealed several interesting phytochemicals, including a variety of flavonoids and tannins. The antibacterial activity and lack of toxicity of the P. niruri extracts indicates that they may be worthwhile targets for antibiotic development and further mechanistic and phytochemistry studies are required.